Capacidade de atenuação do solo de fundo da lagoa anaeróbiada ETE de Passo Fundo/RS - Alves, Gislaine Praetorius Mello (2005)
In the current days, there is a larger concern with the environment, mainly because of the transformations that happened due society development. The preservation of the environment will guarantee the life quality of the human beings. Every people generate residues (sewers) that must be treated. The usual methods are Sewers Treatment Stations (STS), which should be correctly designed to avoid excessive infiltration in the soil. The present work has the objective to verify the attenuation capacity of the bottom soil from an anaerobia lagoon of the STS that is being built in Passo Fundo City. It was designed and built two equipments, denominated column and colmatation equipments. It was carried out geotechnical characterization tests and permeability tests of the anaerobia lagoon bottom soil. Also was made the chemical e biological characterization of the effluent (sewers). The parameters analyzed in column equipment were BOD (Biological Oxygen Demand) and COD (Chemistry Oxygen Demand), before and after sewer percolation in the soil samples. The colmatation equipment gave a previous knowledge of the degree of clogging of the bottom soils of the anaerobia lagoon due to sewer disposition. It was measured the permeability variation in function percolation time. The anaerobia lagoon has two soil types: malanic gleysoil, located in the court area and distrofic red latosoil, located in the embankment area. These soils presented permeability values varying of 10-4 cm/s to 10-5 cm/s. The effluent analyzed presented a great variability of parameters values and a high biodegradability. The parameters analyzed in the column equipment demonstrated that have occurred some level of attenuation in the soil, because was observed a reduction COD and BOD after percolation. The soil used in the colmatation equipment presented a permeability reduction, demonstrating that colmatation is beginning in the soil. With the results obtained is possible say that the soils presents a good attenuation capacity, however it will be necessary to use some kind of material with low permeability in court area of the anaerobia lagoon, once the ground water is over ground surface during the winter time